2017
DOI: 10.1308/rcsann.2016.0222
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms, patterns and outcomes of paediatric polytrauma in a UK major trauma centre

Abstract: Introduction Paediatric trauma is a significant burden to healthcare worldwide and accounts for a large proportion of deaths in the UK. Methods This retrospective study examined the epidemiological data from a major trauma centre in the UK between January 2012 and December 2014, reviewing all cases of moderate to severe trauma in children. Patients were included if aged ≤16 years and if they had an abbreviated injury scale score of ≥2 in one or more body region. Results A total of 213 patients were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
40
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 21 publications
14
40
0
5
Order By: Relevance
“…This can be explained in context that most of Saudi people start to drive car at this age. This study in agreement with Elisabeth et al, (8) Gohar Naqvi et al, (20) study, which reported the same thing. Around 16.7% of this study participants did require hospital treatment which means that the injury was trivial.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This can be explained in context that most of Saudi people start to drive car at this age. This study in agreement with Elisabeth et al, (8) Gohar Naqvi et al, (20) study, which reported the same thing. Around 16.7% of this study participants did require hospital treatment which means that the injury was trivial.…”
Section: Resultssupporting
confidence: 93%
“…This is can be explained by the uncommon pedestrian trauma in Saudi Arabia in general and most of RTAs are victims in our study either were drivers or passengers. This in agreement with Sharma et al, (17) Hyder et al, (19) This against Kundal, et al, (5) Gohar Naqvi et al, (20) study in which the most cases of trauma were caused by RTA. The involvement of male and female children is more or less equal in both RTA and fall in our study.…”
Section: Resultssupporting
confidence: 89%
“…The study conducted by G Naqvi et al 2017, revealed highest proportion of pediatric trauma admissions in the third quarter of the year. 19 One previously published study reported increased frequency of pediatric trauma admissions in spring and summer months. 20 Due to the biological, behavioral, social and cultural factors, males are more prone to be involved in injuries.…”
Section: Discussionmentioning
confidence: 98%
“…Именно потому лечение политравмы сопряжено с большими трудностями [1,2]. Однако, большие сложности возникают при оказании помощи детям с политравмой не только на догоспитальном этапе, но и в период стационарного лечения травматиче-ского шока [3,4]. В то же время объективно анализировать патологические процессы без классификации -задача, чаще всего, нереальная, поскольку классификация любой болезни и, тем более -травматической, предполагает оценку, как минимум, по тяжести и динамике развития.…”
Section: Introductionunclassified